Rmanj, an Orthodox monastery on the Triplex Confinium - perceptions and myths, 15th - 18th centuries - Roksandić, Drago (Array, 2007)
A long, early modern history of the Serbian Orthodox Monastery Rmanj, close to the Triplex Confinium itself, has been controversial over the 19th and 20th centuries. Lack of evidences and conflicting appropriations of its heritage in Serbian Orthodox, Croatian Catholic and Bosnian Muslim perspectives raise a large variety of questions on facts myths related to it.